The complete chloroplast genome sequence of Populus davidiana (Salicaceae). Issue 3 (2nd July 2020) - Yu, Haiyan; Zhang, Li; Zang, Jin; Xiao, Liandong; Luo, Jiancheng
Abstract: The complete chloroplast genome sequence of Populus davidiana was characterized from Illumina pair-end sequencing. The chloroplast genome of P. davidiana was 156, 868 bp in length, containing a large single-copy region (LSC) of 84, 976 bp, a small single-copy region (SSC) of 16, 606 bp, and two inverted repeat (IR) regions of 27, 643 bp. The overall GC content is 30.70%, while the correponding values of the LSC, SSC, and IR regions are 64.6%, 69.2%, and 60.1%, respectively. The genome contains 131 complete genes, including 86 protein-coding genes (62 protein-coding gene species), 37 tRNA genes (29 tRNA species) and 8 rRNA genes (4 rRNA species). The Neighbour-joining phylogenetic analysis showed that P. davidiana and Populus rotundifolia clustered together as sisters to other Populus species.